Challenges of social participation management during the COVID-19 pandemic – the case of participatory budgets in big cities in the Łódzkie region - Wiśniewska, Magdalena (Wyzwania wobec zarządzania partycypacją społeczną – przypadek budżetów obywatelskich w miastach regionu łódzkiego, 2022)
COVID-19 has changed both society and the economy. Therefore, it has significantly influenced local communities and their ability to fulfill public needs. Social interactions have been essentially limited, and the revenues of local communities’ budgets substantially reduced. The paper refers to the new and not yet thoroughly studied process of social participation during the COVID-19 pandemic. The aim was to examine whether and how the pandemic affected the process of social participation which is considered one of the most significant ways of adjusting public services to the needs of the citizens. Participatory methods of public management are also consistent with the new paradigm of public management, the public value concept. The author studied participatory budgets in cities in the Łódzkie region. The research consisted in desk research and online questionnaires, and revealed that the participatory activities were limited in their scope, and that there were obstacles which hindered their management.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 1, s. 151-167
Keywords: public management; public value management; social participation; participatory budget; zarządzanie publiczne; zarządzanie wartością publiczną; partycypacja społeczna; budżet obywatelski